2011
DOI: 10.1177/1359105310390247
|View full text |Cite
|
Sign up to set email alerts
|

High trait self-control predicts positive health behaviors and success in weight loss

Abstract: Surprisingly few studies have explored the intuitive connection between self-control and weight loss. We tracked participants’ diet, exercise and weight loss during a 12-week weight loss program. Participants higher in self-control weighed less and reported exercising more than their lower self-control counterparts at baseline. Independent of baseline differences, individuals high in dispositional self-control ate fewer calories overall and fewer calories from fat, burned marginally more calories through exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(141 citation statements)
references
References 29 publications
12
125
0
4
Order By: Relevance
“…In addition, the present approach might be useful beyond performance-related contexts. Crescioni et al (2011) recently found that participants were more successful in reaching the general goal to lose weight the higher their self-control capacity. Similar studies might find individuals' specific minimal weight loss goals (e.g., losing at least 10 lb within the next ten weeks) combined with their self-control capacity to predict weight loss particularly accurately.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the present approach might be useful beyond performance-related contexts. Crescioni et al (2011) recently found that participants were more successful in reaching the general goal to lose weight the higher their self-control capacity. Similar studies might find individuals' specific minimal weight loss goals (e.g., losing at least 10 lb within the next ten weeks) combined with their self-control capacity to predict weight loss particularly accurately.…”
Section: Discussionmentioning
confidence: 97%
“…In general, the evidence suggests that in low power situations, people have less positive affect and more negative affect than those in high power. Those in low power experience more fear, guilt, and shame, 1 Although high self-control predicts effective engagement in positive health behaviors such as exercise and controlled caloric consumption (e.g., Crescioni et al, 2011), these behaviors are multiply determined. Additional macro-level processes are beyond the scope of this analysis.…”
Section: Emotion Regulationmentioning
confidence: 99%
“…This is especially true of healthy eating behaviours; in the current 'obesogenic' environment in which palatable but unhealthy foods are highly visible and readily available, it is often necessary to override temptation to overindulge in such foods in order to maintain a diet that is consistent with long-term health goals (Johnson, Pratt, & Wardle, 2012). Indeed, relatively high dispositional self-control has been associated with healthier eating patterns during a weightloss programme (Crescioni et al, 2011) and in general (Gerrits et al, 2010;Junger & van Kampen, 2010;Sproesser, Strohbach, Schupp, & Renner, 2011), as well as with concomitant health outcomes such as greater success in a weight-loss programme (Crescioni et al, 2011) and lower body mass index (BMI) in general (Crescioni et al, 2011;Junger & van Kampen, 2010;Keller & Siegrist, 2014). When individuals have recently exerted self-control, they are said to be 'depleted' (Baumeister & Alquist, 2009).…”
Section: Introductionmentioning
confidence: 96%